Endothelial dysfunction correlates with plasma fibrinogen and HDL cholesterol in type 2 diabetic patients with coronary artery disease - Bosevski, M; Borozanov, V; Peovska, I; Georgievska-Ismail L (My University, 2007)
Objective: Assessment of endothelial dysfunction (ED) in type 2 diabetic patients with coronary artery disease (CAD) and estimation of correlation of ED with metabolic parameters: low HDL, hypertriglyceridemia, obesity, systolic blood pressure and with inflammatory-hemostatic parameters: CRP and fibrinogen. Patients and methods: 42 patients (age 60.0 +/- 8.5 years) with diagnosed type 2 diabetes and CAD were randomly included in a cross sectional study. B-mode ultrasound system with a linear transducer 7.5 MHz was used for evaluation of flow mediated vasodilation in brachial artery (FMV). FMV was presented as the percentage increase in brachial artery diameter, within 30 s after limb ischemia, previously provoked by cuff inflation. Percentage value up to 10% was defined as ED. Results: Bivariate linear correlation model presented significant correlation between plasma fibrinogen and FMV percentage, with r -0.47, p < 0.01. Presence of ED correlates linearly with plasma level of HDL < 1.03 mmol/L (r -0.35, p < 0.03). Multivariate analysis using Backward Wald model presented fibrinogen (OR 3.14, 95% CI 0.87-11.28) and low HDL (OR 5.16, 95% CI 0.53-60.39) as factors correlated with the presence of endothelial dysfunction. Conclusion: These results presented plasma fibrinogen level and low HDL < 1.03 mmol/L as factors, independently correlated to the presence of endothelial dysfunction in type 2 diabetic patients with coronary artery disease (Tab. 8, Fig. 1, Ref. 25). Full Text (Free, PDF) www.bmj.sk.